The Effect of Organizational Change and Development Management on Sustainable Development - Alwetwat, Tawfik Faraj Suliman (Zenodo, 2023)
This article aims to investigate the impact of corporate change and development management on sustainable development within companies. By the interaction between corporate transformation processes and sustainable development goals, the study aims to identify the best practices and strategies that can help achieve long-term success. In this process, it aims to identify the best practices and strategies that can help businesses while maintaining their economic, social and environmental sustainability commitments.
Keywords: Organizational Change; Development Management; Sustainable Development; Behavioural Economy; Davranışsal İktisat; Organizational Change, Development Management, Sustainable Development; 9. Industry and infrastructure; 11. Sustainability; 12. Responsible consumption